2021
DOI: 10.3389/fpls.2021.661842
|View full text |Cite
|
Sign up to set email alerts
|

Production of Organic Acids by Arbuscular Mycorrhizal Fungi and Their Contribution in the Mobilization of Phosphorus Bound to Iron Oxides

Abstract: Most plants living in tropical acid soils depend on the arbuscular mycorrhizal (AM) symbiosis for mobilizing low-accessible phosphorus (P), due to its strong bonding by iron (Fe) oxides. The roots release low-molecular-weight organic acids (LMWOAs) as a mechanism to increase soil P availability by ligand exchange or dissolution. However, little is known on the LMWOA production by AM fungi (AMF), since most studies conducted on AM plants do not discriminate on the LMWOA origin. This study aimed to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 96 publications
0
17
0
2
Order By: Relevance
“…However, previous studies have indicated that the amount of carboxylates in the rhizosphere decreased when the plants were colonized with AMF (Ryan et al ., 2012; Nazeri et al ., 2014). This could be due to the release of organic acids by AMF through hyphal exudates for the uptake of P (Tawaraya et al ., 2006; Andrino et al ., 2021). As we have not measured the rhizosphere carboxylates, we speculate that the higher abundance of organic acids in roots of AMF treatments that exhibited a mutualistic phenotype could be potentially because AMF managed to uptake P by utilizing the hyphal exudates.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have indicated that the amount of carboxylates in the rhizosphere decreased when the plants were colonized with AMF (Ryan et al ., 2012; Nazeri et al ., 2014). This could be due to the release of organic acids by AMF through hyphal exudates for the uptake of P (Tawaraya et al ., 2006; Andrino et al ., 2021). As we have not measured the rhizosphere carboxylates, we speculate that the higher abundance of organic acids in roots of AMF treatments that exhibited a mutualistic phenotype could be potentially because AMF managed to uptake P by utilizing the hyphal exudates.…”
Section: Discussionmentioning
confidence: 99%
“…Since iron is required for virtually all biological systems, in A. niger , citric acid was demonstrated to function as iron siderophore to increase the bioavailability of iron represented as Fe(III) citrate 38 . Moreover, arbuscular mycorrhizal fungi such as Rhizophagus irregularis secretes a significant amount of organic acids (acetic, butyric, lactic, citric gluconic, malic, and oxalic acids) to sequester low-accessible phosphorus from Fe oxides 39 . Combining our results, it seems that the production of organic acids is such a critical mechanism to help fungi survive under metal-rich environments.…”
Section: Discussionmentioning
confidence: 99%
“…strains were able to solubilize phosphate and to become strongly attached to R. irregularis mycelium (Taktek et al, 2015 ), while 12 out of 128 bacterial strains isolated from Rhizoglomus irregulare mycelium showed phosphate-solubilizing activity (Sharma et al, 2020 ) and 70% of bacteria isolated from R. irregularis spores were able to mineralize P (Battini et al, 2016 ). The mechanism underlying such activities was ascribed to the production of organic acids by AMF and associated microbiota (Andrino et al, 2021 ). A recent study reported that phosphate solubilising bacteria migrated along extraradical AMF mycelium toward a phytate source, which they were able to mineralise (Jiang et al, 2021 ).…”
Section: Amf-associated Bacteria and Possible Role In P Uptakementioning
confidence: 99%